EN TORNO A RUTINAS, DERIVAS Y VARIACIÓN EN LA MORFOSINTAXIS HISTÓRICA HISPANOAMERICANA - Juan Pedro SÁNCHEZ-MÉNDEZ (Studia Universitatis Babeş-Bolyai. Philologia, 2022)
On Routines, Drifts and Variation in Spanish-American Historical Morphosyntax. This work is a theoretical approach in which, in the first place, we set out and discuss the key points that will serve to establish the identification of the main characteristics that a Hispano-American historical grammar would have. Secondly, it offers an attempt to resituate Hispano-American historical grammar in a new perspective and possible lines of research. Thus, the specificities of historical American morphosyntax within Spanish morphosyntax will be presented in order to point out, by way of synthesis, the patterns that would characterize or define the American aspect of morphosyntax in its historical constitution. These will be presented here, by way of analogy, with the terms of routine, drift and variation.